Characterizing the contribution of external obstructions on building daylighting evaluation - Pereira, Roberto Carlos (2008)
The computer simulation is one of the best methods for daylighting analysis. Nowadays, there are dozens of programs to evaluate daylight distribution in the built environment that highly depends on the amount and direction of the incoming light. The sky vault and the surroundings are the main sources of daylight. The illumination produced by the sky depends on its luminance distribution and, to describe it, most of the programs uses standardized sky models. Difficulties on precisely characterizing the daylight sources can produce significant discrepancies between the simulation and the daylight conditions in real environments. Several studies indicate that to ignore the surroundings and the sky luminance dynamic distribution can represent one of the simplifications with more influence on the daylight evaluation. The aim of this research is to develop a method to analyze the contribution of sky vault and surroundings on daylight in an integrated basis, using the luminance digital mapping and computer simulation. In this way, sky and surroundings luminance patterns were introduced into lighting simulation so that the absolute accuracy of the program could be evaluated without the uncertainties that are introduced when sky models are used. One were able to verify that the surroundings, visible to most of the internal environment, when are considered in an appropriate way in the computer simulation, account for a significant portion of the admitted daylight. The outcomes of this research identified an average contribution up to 26% in the inner illuminance levels produced by lateral windows. The developed procedure also showed to be adequate for evaluating computer codes that aim the prediction of time-varying illuminances founded on climatic test reference year data.